Are we social enough for social media? A study of social media use within Icelandic public libraries - Katrín Níelsdóttir 1981- (2017)
The purpose of this research was to study the use and role of social media within Icelandic public libraries. Requests for interviews were sent electronically to 11 public libraries within the greater Reykjavík area. I received seven replies which resulted in nine qualitative interviews. The intention of this research was to add knowledge to the subject area as research had not yet been conducted on public library social media use in Iceland. While research within Iceland was not available at the time of writing, there has been extensive research done internationally. Participants in the current study perceived social media as a useful tool for library use and the majority were very positive about their library’s use of social media. The participants viewed social media as a way to improve the library image as well as a useful marketing tool. This included reaching out to target groups and advertising library events. While choosing forms of social media for the library, the participants preferred to use the same forms that they used for their personal social media use. When using social media, the participants expressed a considerable amount of uncertainty regarding creating content and using social media forms that they did not have personal experience with. The participants felt that social media use was supported by library management but not actually managed. The participants lacked training that could give them the confidence to explore other forms of social media while creating content for the forms that are currently in use. Other concerns included a lack of co-operation between libraries. The majority of participants expressed a need for guidelines and schedules to help facilitate their library’s social media use.